Analysis of the burden of gastrointestinal diseases between 1990 and 2017 in China - Lu-Yao LI; Zhong-Li ZHENG; Xin-Li GAN; Xing-Pei GUO; Hao ZI; Zhi-Yuan JIAN; Xue-Qun REN; Xian-Tao ZENG (Yixue xinzhi zazhi)
Objective To compare and analyze the disease burden of gastro-intestinal diseases in China between 1990 and 2017. Methods The Global Burden of Disease Study 2017 was searched for the following indicators: morbidity, mortality, disability adjusted life years (DALY), year of life lost (YLL), and years lived with disability (YLD) which were then analyzed. The gastrointestinal disease burden characteristics of people of different genders and ages were explored. Results Between 1990 and 2017, the incidence of 8 gastrointestinal diseases increased. The top three standardized DALY were malignant gastrointestinal tumors: comprising gastric cancer (391.66 per 100,000), esophageal cancer (222.58 per 100,000) and colorectal cancer (216.19 per 100,000). The only increase in standardized mortality was for colorectal cancer which increased by 8.20%, from 9.33 per 100,000 to 10.10 per 100,000. The burden of disease increases with age. Compared with females, males have lower incidence of gastrointestinal diseases, but mortality and DALY rates are higher. Conclusion The burden of disease caused by malignant gastrointestinal tumors accounts for the main burden of gastrointestinal diseases in China, and men are higher than women. Malignant tumors such as colorectal cancer are the focus of prevention and control measures for gastrointestinal diseases.